Nurses' experiences of supporting patients requesting voluntary assisted dying: A qualitative meta-synthesis - Sandham M; Carey M; Hedgecock E; Jarden R (John Wiley and Sons Ltd, 2022)
Aim: Describe the reported lived experiences of nurses who have participated at any stage of voluntary assisted dying (VAD), from the initial request to the end of life. Design: A qualitative meta-synthesis. Data sources: Databases searched were CINAHL, MEDLINE, Emcare, Scopus and PsycInfo. The search was undertaken in September 2021 with no date limitations. Qualitative studies were considered if published in English, reported primary data analysis of nurses' experiences who had been involved in VAD and reported direct quotes from nurses. Review methods: Qualitative studies meeting the selection criteria were critically appraised, then an open card-sort method was applied. Quotes from nurses were organized to group similar experiences, constructing themes and metaphors across studies as a new understanding of nurses' experiences of VAD. Results: Eight studies were included. Three major themes were constructed: An orderly procedure, reflecting the need for structure to feel adequately prepared; A beautiful death, reflecting the autonomy the patient exercised when choosing VAD facilitated an exceptionally positive death; and Psychological and emotional impact, where nurses recognized the emotional and ethical weight that they carried for themselves and the team when undertaking VAD. Conclusion: Nurses may benefit from clear policy, supervision and communication training to support them as countries transition to providing VAD services. Policy provides nurses with confidence that they are undertaking the steps of VAD correctly and provides a layer of emotional protection. Communication training specific to VAD is necessary to prepare nurses to recognize their own emotional experiences when responding to the needs of the patient and their family. Impact: VAD is increasingly becoming a legal option that nurses are encountering in their professional practice. Understanding nurses' experiences of being involved in VAD is required to support nurses in countries where VAD is becoming available to prepare professionally and psychologically.
Keywords: end-of-life care; medical assistance in dying; nursing; palliative care; qualitative meta-synthesis; qualitative studies; systematic review; voluntary assisted dying